Diagnostic value of electrocardiography for ventricular septal defect - Besse Sarmila; Burhanuddin Iskandar; Dasril Daud (Indonesian Pediatric Society, 2019)
Background Congenital heart disease (CHD) in children requires attention from medical practitioners, because CHDs that are diagnosed early and treated promptly have good prognoses. Ventricular septal defect (VSD) is the most common type of congenital heart disease. Objective To compare the accuracy of electrocardiography (ECG) to echocardiography in diagnosing VSD. Methods This diagnostic study was conducted from November 2013 until July 2015. It involved patients with acyanotic CHDs who were suspected to have VSD at Dr. Wahidin Sudirohusodo Hospital, Makassar, South Sulawesi. Results Of 114 children screened, 97 were included and analyzed. The frequency of positive VSD was 69.1% based on ECG, and 99% based on echocardiography. There was a significant difference between ECG and echocardiography (P=0.000). However, when small VSDs were excluded, there was no significant difference between the two diagnostic tools [(P=1.000), Kappa value was 0.66, sensitivity was 98.5%, specificity was 100%, positive predictive value (PPV) was 100%, and negative predictive value (NPV) was 50%]. Conclusion There were significant differences between the ECG and echocardiography, for diagnosing VSD. However, if small VSDs were not included in the analysis, there was no difference between the two examinations, suggesting that ECG might be useful for diagnosing VSD in limited facilities hospitals.